On the inverse kinematics of an underwater vehicle-manipulator system - Hoang, Nguyen Quang (Vietnam Journal of Mechanics, 2012)
The inverse kinematics plays an important role in the trajectory planning and the control of underwater vehicle-manipulator system. The solutions of this problem have an important influence on the motion quality of end-effectors. This paper presents an improved method based on the Jacobian matrix and the error feedback. By using this method, the accuracy of the solution of inverse kinematics for the vehicle-manipulator system is improved. In addition, one of the advantages of a redundant system is exploited to avoid impact on joint limitations. Numerical simulations in software Matlab are carried out to verify the efficiencies of the proposed method.